The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1042/etls20170047
|View full text |Cite
|
Sign up to set email alerts
|

Organoids, organs-on-chips and other systems, and microbiota

Abstract: The human gut microbiome is considered an organ in its entirety and has been the subject of extensive research due to its role in physiology, metabolism, digestion, and immune regulation. Disequilibria of the normal microbiome have been associated with the development of several gastrointestinal diseases, but the exact underlying interactions are not well understood. Conventional in vivo and in vitro modelling systems fail to faithfully recapitulate the complexity of the human host-gut microbiome, emphasising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 158 publications
(219 reference statements)
0
16
0
Order By: Relevance
“…For drug‐secreting bacteria, it is necessary to understand the microenvironment conditions that dictate pharmacokinetic parameters. Recent work has shown that in vitro preclinical models can be used to recreate interactions within and between the microbiota, human host, and the microenvironment to study complex biological interactions . While these systems are in their infancy, both static and dynamic in vitro models can be used identify and evaluate microbe therapeutics, providing valuable information that can inform formulation approaches.…”
Section: Preclinical Approaches To Improve Microbe‐deliverymentioning
confidence: 99%
“…For drug‐secreting bacteria, it is necessary to understand the microenvironment conditions that dictate pharmacokinetic parameters. Recent work has shown that in vitro preclinical models can be used to recreate interactions within and between the microbiota, human host, and the microenvironment to study complex biological interactions . While these systems are in their infancy, both static and dynamic in vitro models can be used identify and evaluate microbe therapeutics, providing valuable information that can inform formulation approaches.…”
Section: Preclinical Approaches To Improve Microbe‐deliverymentioning
confidence: 99%
“…In addition to the establishment of several specific disease models, organoids can be used for high-throughput drug screens [75]. A variety of organoid-based high-throughput screen systems have been established, such as organoid-on-chip [76,77]. As there is a strong correlation between gene mutation status and the therapeutic response, known as mutation-based drug sensitivity [78], the adoption of the tumor organoids has been used in precise cancer therapy.…”
Section: Applications In Personalized Therapymentioning
confidence: 99%
“…Skrede & Westgaard 45 Guerineau et al 78 Barbara et al 84 De Kanter et al 99 Toran-Allerand 16 Navratil et al 79 Petrovic et al 83 De Graaf et al 100 O'Rourke et al 52 Alim et al 80 DeNardi et al 87 Li et al 101 Wray et al 50 Schwerdtfeger et al 96 Tobet et al 70…”
Section: Slicesmentioning
confidence: 99%
“…They are known to influence tissue physiology and have been suggested to decrease intestinal motility, 97 as well as regulate certain enteric neuronal subtypes 98. Slicing intestines became a useful approach for metabolic and toxicological studies in the 2000s 99. Precision cut intestinal slices 100 (PCIS) were first used to study gut drug metabolism capabilities101 and subsequently to characterise the intestinal response to toxins 102.…”
mentioning
confidence: 99%